Bacteriological Quality of Drinking Water Sources and Reservoirs Supplying Dharan Municipality of Nepal - Pant, Narayan Dutt; Poudyal, Nimesh; Bhattacharya, Shyamal Kumar (Annals of Clinical Chemistry and Laboratory Medicine, 2016)
BACKGROUND: Nepal is one of the least developed countries and in most of the areas the water supplied directly from natural water sources (like streams, rivers etc.) is used for drinking purpose, without any prior treatment. So every year there are many water related outbreaks mainly in rainy season. Very little data is available about the bacteriological quality of the water from drinking water sources, in the country. This report presents a scenario of the bacteriological quality of the water from drinking water sources and reservoirs, supplying Dharan municipality of Nepal. METHODS: Bacteriological analysis of the water samples was performed by membrane filter technique and spread plate technique. Total coliform count (TCC), fecal coliform count (FCC) and fecal streptococcal count (FSC) were performed by using membrane filter technique and total plate count (TPC) was performed by spread plate method. RESULTS: Most of the sources and reservoir tanks were found to be heavily contaminated with heterotrophic bacteria, total coliforms, fecal coliforms and fecal streptococci. Contamination with more than one types of indicator organisms was common. CONCLUSIONS: Most of the sources and reservoirs were found to be heavily contaminated with indicator organisms suggesting the alarming situation of water pollution in the area. Abrupt action is needed to be taken to improve the bacteriological quality of the water sources and reservoirs, supplying drinking water to Dharan municipality of Nepal.